Hyaluronic Acid as a Mechanism to Mitigate the Effects of Face Lower Third Aging in Dentistry: A Review - Helena Martins; Inês Carpinteiro; Paulo Mascarenhas; Margarida Goes; Henrique Oliveira (Applied Sciences, 2023)
Aging can have a negative impact on the perioral region, affecting both appearance and self-esteem. Dentists offer various treatment options to address these changes, using surgical and non-surgical techniques. One such technique is facial filling with hyaluronic acid, a minimally invasive approach to improve the perioral region’s function and aesthetics and counteract aging effects. A literature review was conducted to collect scientific evidence on the subject, utilizing the mnemonic PI(C)O to refine the research question. The search for articles was accomplished on the EBSCOhost platform, specifically targeting those published between January 2009 and April 2023 in MEDLINE Complete, CINAHL Complete, and MedicLatina databases. Sixteen articles were carefully chosen, and the guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) method were followed throughout the process. The major findings reported in the selected articles suggest that using hyaluronic acid as a mechanism to mitigate the effects of face lower third aging following orofacial harmonization procedures in dentistry offers significant benefits to patients, improving the aesthetic appearance of the face, increasing patients’ self-esteem and satisfaction, and providing a better quality of life. Nevertheless, a weak evidence level was found in the selected articles due to methodological issues, highlighting the need to increase the methodological quality of future studies.